Accelerated magnetic resonance imaging - Hong, Xinying. (2011)
Magnetic Resonance Imaging (MRI) is a great invention in the biomedical field, it is an instrument which is non-invasive, yet able to image the interior structure of the body and yield information which other techniques could not. This technique is widely used in diagnostic medicine; however it is also commonly used in the oil and food industries. This instrumental technique is safe to use medically as it uses magnetic field, which is proven to be of no harm to the human body. However, this MRI technique has been hampered by long scan time due to physical and psychological constraints. Therefore, Accelerated Magnetic Resonance Imaging is being explored to reduce this scan time which will in turn benefits the patients and economically wise, reduce costs.